Analyzing Alignment of Grade-V Islamic Studies Textbook Published by the Punjab Curriculum & Textbook Board (PCTB) with the Objectives of Single National Curriculum (SNC) - Muhammad Asdaq Hanif, Afshan Naseem, Rizwan Akram Rana (PJE, 2023)
This study was conducted to assess if the Islamic Studies textbook of grade V published by the Punjab Curriculum and Textbook Board, Lahore was aligned with the objectives of teaching Islamic Studies as outlined in the Single National Curriculum (SNC). The qualitative study was conducted by considering the objectives of teaching Islamic studies as outlined in SNC and whether the Islamic Studies textbook of grade V published by Punjab Curriculum and Textbook Board, Lahore succeeds in achieving those objectives. The analysis was done by using two instruments after the literature review. The first instrument is called the Curriculum-Textbook (CT) alignment checklist and considersthe contents of the Islamic Studies textbook published by the Punjab Curriculum and Textbook Board, Lahore book on four basic parameters. The second instrument is called the Curriculum-Textbook Alignment Rubric (C-T Alignment Rubric) which considered the contents of a Grade V Islamic Studies textbook published by Punjab Curriculum and Textbook Board, Lahore on a wide range of parameters. The results of the study revealed that the Islamic Studies textbook of grade V was generally aligned with the objectives of teaching Islamic Studies as outlined in the SNC. However, the textbook did not adequately address one of the core objectives of the SNC: to promote social inclusiveness and religious harmony. It is recommended that future editions of the textbook should incorporate these fundamental objectives of SNC to create an inclusive and tolerant society which was one of the primary objectives of the Single National Curriculum (SNC).